(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
This article explores the implementation of smart homes using the Internet of Things (IoT) through Cisco Packet Tracer 7.0. It discusses the design and configuration of smart networks that integrate home automation, security, and intelligent vision technologies. The article addresses the application of Packet Tracer in the setup and configuration of complex smart networks as part of smart home systems, including appliances, security systems, and intelligent vision technologies. The implementation outcome simulates the concept of smart homes supporting various automation systems and demonstrates Packet Tracer’s feasibility as a powerful tool for designing and installing smart home systems. The Packet Tracer simulator provides a variety of IoT devices that allow for quicker and easier design and implementation of a smart home system before it is implemented in actual environments. It provides the ability to combine wireless networks, sensors, and monitoring or tracking devices for increased system integration and pervasive security and control within home settings. Automation is done effortlessly using pre-defined control rules for all devices that are connected and without the necessity of complex programming skills, making systems safer and more efficient. Such outcomes advance the vision of smart and integrated smart homes, and show how cutting-edge technologies can help make lives better and create a safe and comfortable environment.